PERFORMANCE CORRECTION FACTORS FOR VAPOR COMPRESSION REFRIGERATION AND HEAT PUMP SYSTEMS TESTED WITH UNCONTROLLED CONDENSER CONDITIONS - Nobre, G. M.; Vasconccelos, A. A.; Cárdenas Gómez, A. O.; Bandarra Filho, E. P.; Parise, J. A. (Revista de Engenharia Térmica, 2017)
A method for experimental data adjustment consisting of correction equations for the performance parameters of the refrigeration/heat pump vapor compression cycle, when operation conditions depart from those established in testing standards, is here presented. A basic thermodynamic model allowed for a methodology to be developed so as to correct vapor compression cycle performance to a desirable operating condition. Correction factor equations are proposed for refrigerant mass flow rate, compressor specific enthalpy gain and evaporator refrigeration effect, for situations when condensing pressure has not followed standards conditions or has not been properly controlled during experiments. The method was verified against experimental data from a vapor compression water-to-water heat pump with controlled condensing temperatures of 30oC, 40oC and 50oC. In spite of the purposely excessive correction, ±10oC, a relatively good smoothness, as well as a good agreement among all conversions, was obtained with the standardized points. The model was also applied to a refrigeration system running with water-SWCNT nanofluid (single walled carbon nanotube with water as the base fluid) as the secondary fluid. It contributed to a better discernment of the actual influence of the nanofluid in the system performance.